(untitled) (Research, Society and Development, 2023)
The objective of this article was to analyze the Environmental Licensing process for evaluate its effectiveness in reconciling economic development and environmental preservation. To this end, the assessment of environmental quality will be studied in the licensing process, which aims to ensure that the proposed activity is carried out in a manner compatible with the preservation and protection of the environment, avoiding significant adverse impacts, where the National Environmental Policy (PNMA), is a fundamental legal framework in Brazil for environmental management and licensing of activities that may impact the environment. The types of license are defined by the legislation of each country and it´s obtaining is an administrative process through which environmental bodies assess the feasibility and conditions for the installation, expansion or operation of enterprises that use natural resources or may cause environmental impacts. The result shows that environmental licensing is a valuable tool in the search for a balance in environmental preservation. However, it is important to recognize the challenges it presents by working to improve the process, ensuring it is effective, transparent and fair for all parties involved. Collaboration between governments, businesses and communities is essential to ensure that licensing fulfills its purpose in an efficient and sustainable way. It is concluded that environmental licensing represents a significant advance in the protection of the environment and the legislation and that it is possible to observe that over the last 40 years the environmental issue has gained prominence in day-to-day concerns.